Analisis Hasil Investasi, Premi Dan Beban Klaim Terhadap Laba Perusahaan AIA Prudential Di Kota Juang Kabupaten Bireuen - Sri Yanna (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This type of research is quantitative, the place of this research is the AIA Prudential Office in Juang City. This writing aims to analyze investment returns, premium income, and claim expenses on profits using partial correlation, determination and multiple linear regression. The data collection method in preparing the final assignment is the observation method and documentation study using quantitative analysis. The analysis technique is multiple linear regression using SPSS 20 software. In this research the data used is secondary data. From the results of the partial correlation coefficient test, it is found that investment returns and premium income have a significant relationship to profits, positive values ​​of 1,750 and 2,305 mean strong and unidirectional guarantees, meanwhile, claim expenses have a significant relationship to profits, a positive value of 3,704 means strong guarantees and strong in the opposite direction, simultaneously (together) shows that investment returns, premium income, claims expenses have a significant relationship to profits.